2019
DOI: 10.1002/14651858.cd011257.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Couple and family therapies for post-traumatic stress disorder (PTSD)

Abstract: The objectives of this review will be to: 1. assess the efficacy of couple and family therapies for adult PTSD, relative to 'no treatment' conditions, 'standard care', and structured or non-specific individual psychological therapies; 2. examine the clinical characteristics of studies that influence the relative efficacy of these therapies; and 3. critically evaluate methodological features of studies that bias research findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…However, they suggest that the strategies of noticing and responding to early indications of anger and momentary changes in anger, as in CBCT for PTSD, are likely to be effective in reducing the overall variability of anger if they are successful in reducing the intensity of anger outbursts. Overall, the present findings support clinical strategies to simultaneously address symptom accommodation and PTSD symptoms as well as strategies to increase emotional disclosure in the service of reducing symptoms like emotional numbing and avoidance, as used in dyadic treatments for PTSD (Suomi et al., 2019).…”
Section: Discussionsupporting
confidence: 76%
“…However, they suggest that the strategies of noticing and responding to early indications of anger and momentary changes in anger, as in CBCT for PTSD, are likely to be effective in reducing the overall variability of anger if they are successful in reducing the intensity of anger outbursts. Overall, the present findings support clinical strategies to simultaneously address symptom accommodation and PTSD symptoms as well as strategies to increase emotional disclosure in the service of reducing symptoms like emotional numbing and avoidance, as used in dyadic treatments for PTSD (Suomi et al., 2019).…”
Section: Discussionsupporting
confidence: 76%
“…ANGER AND PTSD AMONG VETERANS 341 targets for novel PTSD treatments (Suomi et al, 2019). The findings would seem to have implications for treatment and suggest that veterans with anger problems would benefit from a preliminary phase addressing anger; for example, via cognitive-behavioral anger interventions (Lee & DiGiuseppe, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it seems likely that anger would increase negative interactions with others and reduce social resources that can promote symptom change. Such resources may include qualities of the therapeutic alliance with treatment providers (Chemtob et al, 1997) as well as family relationships that provide important “recovery environments” (Johnson & Williams-Keeler, 1998) and targets for novel PTSD treatments (Suomi et al, 2019). The findings would seem to have implications for treatment and suggest that veterans with anger problems would benefit from a preliminary phase addressing anger; for example, via cognitive-behavioral anger interventions (Lee & DiGiuseppe, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging data suggest that PTSD affects not only the victims' physical and mental health but also those of their friends and family members. It was shown that families with a member suffering from PTSD experienced low relationship pleasure, incidents of familial violence and a negative effect on the family members' mental health [39]. This issue and other important issues of diverse PTSD such as late-onset PTSD (PTSD that primarily erupts six-months or more after the occurrence of the traumatic event) [40] and complex PTSD (PTSD that occurs as a result of exposure to chronic, multiple or repeated traumas, that an escape from them is considered difficult or even impossible) [41] should also be tested for the effect of PARP inhibition.…”
Section: Discussionmentioning
confidence: 99%